Intrinsic FGFR2 and Ectopic FGFR1 Signaling in the Prostate and Prostate Cancer - Wang, Cong; Liu, Ziying; Ke, Yuepeng; Wang, Fen (Frontiers in Genetics, 2019)
Advanced castrate-resistant prostate cancer (CRPC) is a poorly prognostic disease with no effective cures currently. Understanding the molecular mechanism that underlies the initiation and progression of CRPC will provide new strategies for this deadly disease. One candidate pathway is the fibroblast growth factor (FGF) signaling axis. Loss of the resident FGF7/FGF10-type 2 FGF receptor (FGFR2) pathway and gain of the ectopic type 1 FGF receptor (FGFR1) pathways are associated with the progression to malignancy in prostate cancer (PCa) and many other epithelial originated lesions. Although FGFR1 and FGFR2 share similar amino acid sequences and structure domains, the two transmembrane tyrosine kinases elicit distinctive, even sometime opposite signals in cells. Recent studies have revealed that the ectopic FGFR1 signaling pathway promotes PCa progression via multiple mechanisms, including promoting tumor angiogenesis, reprogramming cancer cell metabolism, and potentiating inflammation in the tumor microenvironment. Thus, suppression of FGFR1 signaling can be an effective novel strategy to treat CRPC.